Resilience among people who face natural disaster (Journal of Psychiatrists' Association of Nepal, 2017)
Human beings possess the power to resist an adverse situation and this unique characteristic is one of the basic instinct to survive. Individual capacity to deal with insurmountable adversities is a matter of great astonishment. Often physical capacity fails but drive and conviction to survive in difficult situations persist and remains source of strength. In language of understanding it is referred to an internal capacity to fight. A number of people refer to this as ‘resilience’. There are about seventy definitions of the term resilience. The Oxford dictionary defines it as ‘the capacity to recover quickly from difficulties and toughness’. Considering most of the references to tern resilience it appears to be ‘human capacity to deal with adverse situations and quickly bounce back to normalcy’.